Interdisciplinary study on environmental support and cognitive regulation enhancing music creativity in Orff Schulwerk for non- music major college students - Jinyi Yu; Marissa Ejercito - Borines (Environment and Social Psychology, 2025)
Based on an interdisciplinary perspective, this study explores the mechanisms by which environmental support and cognitive regulation enhance musical creativity among non-major university students in Orff improvisation. A quasi-experimental design was employed, selecting 400 non-major university students as research participants. The experimental group received Orff improvisation instruction integrated with environmental support and cognitive regulation strategies, while the control group received traditional music instruction, with an intervention period of 16 weeks. The study utilized mixed methods, collecting data through questionnaire surveys, behavioral observations, work analysis, and in-depth interviews, and analyzing the data using descriptive statistics, analysis of variance, regression analysis, and structural equation modeling. The results indicate: (1) Environmental support and cognitive regulation demonstrate significant synergistic effects; when environmental support reaches optimal configuration, students’ cognitive regulation efficacy improves by 67.3%, and overall musical creativity enhances by 78.2%; (2) The three stages of Orff improvisation present differentiated environment-cognition interaction patterns: the imitation stage primarily optimizes cognitive load, the exploration stage promotes metacognitive development, and the improvisation stage releases cognitive freedom; (3) Demographic characteristics play important moderating roles in environment-cognition interactions, with gender differences mainly manifested in environmental support preferences and age differences reflected in the maturity of cognitive regulation strategies; (4) Musical creativity enhancement is achieved through four pathways: cognitive load optimization, emotional arousal regulation, social belonging construction, and self-efficacy enhancement, demonstrating significant psychological and social effects; (5) The constructed interdisciplinary theoretical framework successfully explains the complex mechanisms of musical creativity development, with the overall model explanatory power reaching 73.4%. The proposed "ecological-cognitive" teaching model provides scientific guidance for music education practice, and the developed assessment tools for environmental support and cognitive regulation establish a foundation for subsequent research. This study enriches the theoretical system of music education, expands the application domains of environmental psychology and cognitive psychology, and provides important theoretical foundations and practical pathways for cultivating innovative talents and promoting students’ comprehensive development.